Packaging para productos alimenticios organicos de la tienda ecológica sami waylla. - Chango Tandalla, Lourdes Gabriela (2018)
The research Project allowed to solve the problem of the packaging for organic food products of Sami Waylla ecological store, the same that possesses a lack visual identity, in its form as in its labeled. It was identified that the packaging to be modified and redesigned are: Neem leaves, turmeric, cardamom and fruit tea, so it is considered that these four organic products should change their presentation in an aesthetic way modifying their visual image, not only of the shape and size also its label and material. For this design process will be supported by Packaging Design research. For the theoretical support was obtained information from Sami Waylla ecological store as the history Mipymes, its institutional values, mission, and vision, among others. With regard to the theoretical information was analyzed about packaging, functions, and characteristics, types of materials, food products, packaging and finishes. It was applied qualitative instruments (interviews) to experts over packaging creation and quantitative (surveys) to customers of the Sami Waylla micro company by means of research tools such as questionnaires based on multiple choice questions. That provided an impartial point of view packaging. The creation and design of the packaging follows an established order by stages that ranges from the sketches until product delivery. In this were established layout elements such as typography, chromatic form of the label, usability testing, prototyping, among others. This process was carried out through the methodology of Ambrose and Harris, which served for the realization of the product through 11 stages that allowed the packaging realization. In conclusion, was obtained aesthetic and communicative visual package that will promote the trade and consumption of organic products in Ecuador, this research will count as a technical impact to be reference for future research, social by promoting local development focusing directly on organic packaging. Environment by motivating the use of biodegradable and organic packaging. Finally, was achieved the innovation of the organic product Packaging of Sami Waylla ecological micro company, being a support and reference of theoretical and practical research.